Therapeutic Communication in Mental Health Nursing : Aesthetic and Metaphoric Processes in the Engagement with Challenging Patients /: Aesthetic and Metaphoric Processes in the Engagement with Challenging Patients. (2017) - Birnbaum, Shira, 1962-
No abstract available